In Vitro Dissolution Profiling and Release Kinetics of Abelmoschus manihot L. Ethanolic Extract Mucoadhesive Granules: A Higuchi Diffusion Model Analysis - Siti Mardiyanti; Nila Isnaini Rahmawati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Peptic ulcer disease presents a persistent clinical challenge characterized by a critical imbalance between mucosal defensive mechanisms and aggressive luminal factors, including Helicobacter pylori infection and non-steroidal anti-inflammatory drug administration. The ethanolic extract of Abelmoschus manihot L. possesses potent antioxidant flavonoids, specifically quercetin, which exhibit significant gastroprotective potential. However, the therapeutic efficacy of conventional herbal extracts is often compromised by rapid physiological gastric emptying. The aim of this study was to formulate gastroretentive mucoadhesive granules containing the ethanolic extract of A. manihot using Hydroxypropyl Methylcellulose (HPMC) as a matrix polymer and to elucidate the drug release mechanism through advanced mathematical kinetic modeling. Methods: The extract was standardized for total flavonoid content and antioxidant activity using the DPPH assay. Mucoadhesive granules were engineered via wet granulation with varying concentrations of HPMC (F1: 15%, F2: 20%, F3: 25%) and a constant 15% Carbopol. The formulations underwent rigorous physicochemical characterization, ex vivo wash-off mucoadhesion testing on porcine tissue, and in vitro dissolution profiling in artificial pH 1.2, 6.8, and 7.4 media. Release data were evaluated using Zero-order, First-order, and Higuchi kinetic models, validated via the Akaike Information Criterion (AIC). Results: The standardized extract demonstrated potent antioxidant activity with an IC50 of 27.14 +/- 1.05 mcg/mL and a high total flavonoid content of 162.8 mg QE/g. All granule formulations exhibited excellent flowability. Formula F3 (25% HPMC) displayed superior swelling capacity (15.2-fold expansion) and mucoadhesion (30.0% retention at 60 minutes). Dissolution testing revealed F3 retarded drug release significantly compared to F1, releasing only 41.92% in pH 1.2 over 6 hours. Kinetic analysis confirmed that F3 strictly followed the Higuchi diffusion model, indicating release governed by diffusion through the swollen polymer matrix. Conclusion: The HPMC-Carbopol mucoadhesive granules of A. manihot successfully achieved sustained release and enhanced structural mucoadhesion. Formula F3 represents a mechanistically sound gastroretentive delivery system, driven by complex polymer hydration dynamics, for the localized management of peptic ulcers.